Conditioned media and DMSO enhance the cryopreservation of bovine adipose tissue-derived mesenchymal stem cells - Irfan, S.; Suyatno, S.; Zulfiqar, H.; Lestari, D. A.; Hafid, A.; Kostaman, T.; Herdis, H.; Priyatno, T. P.; Sitaresmi, P. I.; Hudaya, M. F.; Lupitasari, F. B. I.; Pangestu, M. (Journal of the Indonesian Tropical Animal Agriculture, 2024)
Mesenchymal stem cells derived from adipose tissue (AD-MSCs) show great potential for repro ductive biotechnology in the livestock sector. However, enzyme-based isolation of MSCs is expensive and time-consuming, so it is still rarely done, especially for applications in the livestock sector in de veloping countries. So, MSCs must be cryopreserved with an efficient cryoprotective agent to be stored and reproduced in various laboratories after isolation. This study was aimed to optimize the cryopreser vation media for adipose-derived MSCs in cattle. This study evaluated the viability, proliferation, and morphology of AD-MSCs. The results of this study indicate that a combination of 10% DMSO, 45% DMEM, and 45% conditioned media significantly improves post-thaw viability, proliferation, and sur vival as compared to other mediums. Furthermore, AD-MSCs cryopreserved in this medium exhibit similar morphology as fresh cells. These findings suggest that the optimized cryopreservation medium can enhance the quality and safety of AD-MSCs for clinical applications in the livestock industry.